2020
DOI: 10.1101/2020.04.03.024778
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

From simplicity to complexity: The gain or loss of spot rows underlies the morphological diversity of threeDrosophilaspecies

Abstract: 13To understand how novel animal patterning emerged, one needs to ask how the 14 development of color patterns has changed among diverging species. Here we examine 15 three species of fruit flies -Drosophila guttifera (D. guttifera), Drosophila palustris (D. 16 palustris), and Drosophila subpalustris (D. subpalustris) -displaying a varying number 17 of abdominal spot rows that were either gained or lost throughout evolutionary time. 18 Through in situ hybridization, we examine the mRNA expression patterns for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…wg, dpp , and hh are homologous to known proto-oncogenes in humans 24 , while zen and abdA are Hox genes. The abdominal color pattern of D. guttifera appears to be regulated by multiple developmental pathways consisting of activators and repressors acting in parallel, possibly targeting pigmentation genes other than y as well 18,19,25,26 . Further evidence for the repression of stripes can be seen in Drosophila falleni ’s intraspecific pigment variation, another member of the quinaria species group (Extended Data Fig.…”
Section: Figurementioning
confidence: 99%
“…wg, dpp , and hh are homologous to known proto-oncogenes in humans 24 , while zen and abdA are Hox genes. The abdominal color pattern of D. guttifera appears to be regulated by multiple developmental pathways consisting of activators and repressors acting in parallel, possibly targeting pigmentation genes other than y as well 18,19,25,26 . Further evidence for the repression of stripes can be seen in Drosophila falleni ’s intraspecific pigment variation, another member of the quinaria species group (Extended Data Fig.…”
Section: Figurementioning
confidence: 99%
“…These studies suggest that t is an important player in the evolution of morphological diversity in Drosophila species. Most interestingly, t expression has co-evolved with y expression [22,23], where both genes are co-expressed in the developing adult cuticle of diverse Drosophila species [33]. Although these two genes have been known to be co-expressed over considerable evolutionary time [22,27], very few studies have demonstrated how two or more genes are transcriptionally coupled and regulated.…”
Section: Introductionmentioning
confidence: 99%